ΚΚΕ ΚΑΙ ΣΛΑΒΟΜΑΚΕΔΟΝΙΚΗ ΜΕΙΟΝΟΤΗΤΑ ΣΤΗΝ ΚΑΤΕΧΟΜΕΝΗ Δ. ΜΑΚΕΔΟΝΙΑ (1941-1944) - ΛΥΜΠΕΡΑΤΟΣ, ΜΙΧΑΛΗΣ Π. (Μνήμων, 1998)
Michalis P. Liberatos, The Greek Communist Party and the SlavophonesMinority in West Macedonia during the German Occupation (1941-194 The existence of a Christian Slavic-speaking population in West Macedoniaafter the exchanges of populations in 1923-1924 and its confrontationwith Greek residents affected not only the relations between Greeceand the neighbouring Balkan countries but also determined the attitudeof KKE towards the Greek political stage and its relations with the otherpolitical parties. Especially during the German Occupation in Greece thecontroversies were enforced because of the existence of Bulgarian occupationalauthorities in the region and the attempt of Germans to treatethnic differences as an instrument of oppression. On the contrary, theGreek resistance forces that acted in Macedonia attempted to avert theaccession of Slavophones to Bulgarian nationalism and tried to compromisethe contradictions between the minority and the Greek population.The main resistance movement in the region, EAM, an organisationthat included KKE as the stronger part of it, had the advantage thatit was acceptable to the minority. On the other hand, other Greek organisations,like PAO, caused a feeling of fear, insecurity and mistrust tothe minority as representatives of Greek nationalism. KKE, because of itspolitical attitude towards the defence of the social rights of the minorityin the Inter-War period, had gained the confidence of that population,something extremely useful for the purposes of the liberation struggle.Nevertheless, the other political forces in Greece suspected that KKEhad returned to its attitude about the «Autonomy» of Macedonia fromthe Greek State, which KKE had declared in the decade 1925-1935. Thatwas a great obstacle for a political party that for a long period exerteditself to prove that it had abandoned that policy and especially in relation with EAM, which was based primary on its patriotic character. In orderto avoid the charges that it favoured the Slavophones separatists andthe possibility of an internal crisis that might have dissolved the politicalalliance of EAM, KKE pursued to incorporate the Slavophones into theGreek liberation movement on purpose to create a state of mutual confidencebetween the two populations. At the same time, it tried to isolatethe minority from the propaganda of Bulgarian separatists and destroythe corresponding armed groups.The problems regarding the relations between the minority and theGreek resistance movement became more complicated because of theinvolvement of Tito's regime in Yugoslavia. Tito and his partisans attemptedto use their ideological connection with EAM as a means to persuadeGreeks to accept the existence of minority as a cause of a new arrangementof the borders between Greece and Yugoslavia in the post Warperiod. On the other hand, the leaders of EAM tried to avoid Tito's accusationsthat Greeks impeded the development of a Balkan resistanceco-operation against Axis and strove to confine the massive accession ofSlavophones to the Yugoslavian resistance army by incorporating membersof the minority in organisations of EAM. It was a very difficulttask and often caused more problems than it resolved.